Process‐Improvement Cost Model for the Emergency Department. Issue 6 (November 2015) - Dyas, Sheila R.; Greenfield, Eric; Messimer, Sherri; Thotakura, Swati; Gholston, Sampson; Doughty, Tracy; Hays, Mary; Ivey, Richard; Spalding, Joseph; Phillips, Robin
Abstract : EXECUTIVE SUMMARY : The objective of this report is to present a simplified, activity‐based costing approach for hospital emergency departments (EDs) to use with Lean Six Sigma cost‐benefit analyses. The cost model complexity is reduced by removing diagnostic and condition‐specific costs, thereby revealing the underlying process activities' cost inefficiencies. Examples are provided for evaluating the cost savings from reducing discharge delays and the cost impact of keeping patients in the ED (boarding) after the decision to admit has been made. The process‐improvement cost model provides a needed tool in selecting, prioritizing, and validating Lean process‐improvement projects in the ED and other areas of patient care that involve multiple dissimilar diagnoses.